Application of ICF Rehabilitation Set in China - Tiebin YAN (康复学报)
This study introduces the changes from International Classification of Diseases (ICD), International Classification of Impairment, Disability and Handicap (ICIDH) to International Classification of Function, Disability and Health (ICF); analyzes the reasons for the slow progress of clinical application of ICF; introduces the background, structure and application value of ICF-RS, and explores the application of ICF-RS in China.